The Application of the Analytic Hierarchy Process Approach to the Inheritance of Local Delicious Food Culture and Development of Sustainable Innovations - Yen-Cheng Chen; Ching-Sung Lee; Pei-Ling Tsui; Ming-Chen Chiang (Agronomy, 2022)
Taiwan’s agri-food market has been transforming rapidly over the past few years and is struggling with significant food issues and the impact of COVID-19. These include globalization, trade liberalization, population growth, urbanization, policy changes, food consumption patterns and shifts in dietary patterns. Therefore, food security, livelihoods and productive activities that revitalize rural food production and sustained economic growth need to make important contributions to sustainable rural food development. This study adopts the research method of the Analytic Hierarchy Process, employs agricultural experts as the main research object, focuses on the local cuisine in rural Taiwan, and constructs an index model for the inheritance and sustainable innovation and development of local cuisine culture through the opinions of agricultural experts. Accordingly, this study has two objectives. First, we construct indicators of how farmers use local food culture inheritance and sustainable innovation development. Second, we measure the relative weighting of these indicators by agricultural experts in Taiwan. The research results show that a total of 23 indicators in 5 dimensions of the inheritance and sustainable innovation and development of rural local food culture in Taiwan are obtained, of which education and training are the primary indicators of the inheritance and sustainable innovation and development of farmers’ local food culture. The biggest contribution of this study is that, in response to the threat of the COVID-19 pandemic and the changes in the inheritance and sustainable development of rural food in Taiwan, this research constructs an indicator model for the inheritance and sustainable development of rural local food culture. It can be used as an important reference for the inheritance and sustainable innovation and development of rural local food culture in Taiwan.